Placental Vimentin Expression in Preeclampsia and Gestational Diabetes Mellitus - Asir, Fırat; Oglak, Suleyman Cemil; Korak, Tugcan; Tas, Fatih; Yilmaz, Mehmet; Erdemci, Fikri; Sahin, Firat; Ayaz, Hayat; Yilmaz, Emine Zeynep; Bolluk, Gokhan (Gynecology Obstetrics & Reproductive Medicine, 2024)
OBJECTIVE: This study investigated vimentin expression in placentas of patients with preeclampsia and gestational diabetes mellitus (GDM). STUDY DESIGN: Placentas of preeclamptic women (n=25), women with GDM (n=25), and control cases (n=25) were enrolled in this study. Placental samples were fixed in zinc-formalin and further processed for paraffin wax tissue embedding. Demographic and laboratory parameters of patients were recorded. Vimentin immune activity was analyzed in the placental sections with immunohistochemistry. Sections were imaged and analyzed under a light microscope. A semiquantitative measurement was done between groups by comparing the Vimentin signal and significance was calculated. Network construction and pathway enrichment analysis were conducted using Cytoscape (v3.10.1) and ShinyGO, respectively. RESULTS: Vimentin expression was high in the placental sections of the control group. The preeclampsia group showed positive Vimentin expression in cytotrophoblast and syncytiotrophoblast cells and connective tissue of placental villi in the preeclampsia group. Vimentin expression was generally recorded as negative in placental villi, fibrinoid substances, and connective tissue cells in the GDM group. Bioinformatic analysis showed that the AGE-RAGE signaling pathway and cancer-related pathways were mainly observed in Vimentin-associated pathways, which finally activate inflammatory pathways in both preeclampsia and GDM. CONCLUSION: Vimentin expression patterns in placental tissue sections reveal nuanced regulatory mechanisms, emphasizing the need for further exploration into the functional roles of vimentin in placental physiology and pathology.